Inovasi Dalam Pengelolaan Ruang Terbuka Hijau yang Berkelanjutan di Kota YOGYAKARTA - , Laurencius Martua H, Prof.Ir. Bakti Setiawan, M.A.,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Various functions are attached to the green open space such as the ecological function, the social function, the function of architecture/ aesthetics and economic function have making it an important as a counterweight to the built-up area. Given the importance of the green open space, it would require an innovative and sustainable management. The purpose of this study is to identify the availability of green open space by the standard area, population, and the need for oxygen and find innovations that made by the goverment of Yogyakarta city in the management of green open space. This research was conducted in the city of Yogyakarta after looking at the various achievements in the environmental field obtained Yogyakarta where the presence of green open space become one of the supporting factors. This research used descriptive qualitative method and used sampling techniques such as purposive sampling to the informant who really expert to research topics so that the data and information obtained is valid and objective. This study found that the area of green space in the city of Yogyakarta has fulfilled the mandate of Law Number 26 Year 2007 on Spatial Planning videlicet 30 percent of the administrative area. However, these conditions have not been able to support the needs of the oxygen it needs. Innovative green space management is found in six variety of innovations that made by Yogyakarta City Government. Various innovations took place during the reign of Mayor Hery Zudianto. It shows the importance of a leader 's commitment to deliver sustainable development guidelines. In the future Yogyakarta City Government is expected to continues to innovate and intensification in the management of green open space in order to actualize sustainable development.